Sex Differences Associated With Hepatitis B Virus Surface Antigen Seropositivity Unwareness in Hepatitis B Virus Surface Antigen-positive Adults: 2007-2012 Korea National Health and Nutrition Examination Survey - Suk-Yong Jang; Sung-In Jang; Hong-Chul Bae; Jaeyong Shin; Eun-Cheol Park (Korean Society for Preventive Medicine, 2015)
Objectives: To examine the sex-specific factors associated with being unaware of one's hepatitis B virus surface antigen (HBsAg) seropositivity status in a large, HBsAg-positive population of Koreans. Methods: In total, 1197 subjects aged 19 years or older who were HBsAg-positive according to data from the 2007-2012 Korea National Health and Nutrition Examination Survey were included. Subjects were considered unaware of their HBsAg seropositivity status if they answered that they had no knowledge of being previously infected by the hepatitis B virus (HBV) or diagnosed with HBV hepatitis. Multivariate Poisson regression models with robust variance estimate were used to assess the significance of the variables using weighted frequencies. Results: The majority (77.8%) of HbsAg-positive Korean adults (females, 81.9%; males, 74.6%) were unaware of their HBsAg seropositivity status. We found that sex (female: prevalence ratio [PR] 1.19), household income (low: PR, 1.15), marital status (never married: PR, 1.18), self-rated health (moderate: PR, 1.14; good: PR, 1.12), and alcohol use (at least 2-3 times/wk: PR, 1.21) were associated with being unaware. In females, age (50 to 59 years: PR, 1.29; ≥70 years: PR, 1.30), household income (low: PR, 1.37; middle-low: PR, 1.24), and marital status (never married: PR, 1.33) were associated with being unaware. In males, self-rated health (moderate: PR, 1.14; good: PR, 1.21) and alcohol use (at least 2-3 times/wk: PR, 1.21) were associated with being unaware. Conclusions: Factors related to the socioeconomic status of females and the health-related behaviors of males were found to be associated with being unaware of one's HBsAg seropositivity status.